Cantas Gagal: a revolutionary program uplifting engineering education / Roziah Keria … [et al.] - Keria, Roziah; Md Noor, Noorsuhada; Rhasbudin Shah, Shahreena Melati; Md Hasan, Ahmad Syauqi; Dollah, Zuraisah (Unit Penerbitan PKAPP, 2024)
2023: In an era where academic achievement is paramount, educational institutions are constantly seeking innovative ways to enhance student learning and success. In line with this, a unique initiative known as the "Cantas Gagal" programme was launched in 2016 by former Programme Coordinator EC110 of the Civil Engineering Studies, Universiti Teknologi MARA, Cawangan Pulau Pinang. The Cantas Gagal programme, aimed at strengthening students' understanding of their curriculum, was primarily designed to reduce the failure rates among diploma and bachelor's degree students in Civil Engineering, specifically in the EC110 and EC221 programmes. This ground-breaking initiative brings together experienced lecturers and students to address subjects with high potential for failure or those that have previously shown unsatisfactory results. The ultimate goal is to enhance students' achievement of course outcomes (CO) and programme outcomes (P O).